(untitled) - Batstone, David B. (San Francisco, Calif., 2003)
Saving the Corporate Soul alternates examples of principled companies like Clif Bar and Timberland with those of innovative leaders such as Denny’s CEO Jim Adams, who recovered from a
Keywords: Leadership,Social responsibility of business